Math, asked by ashwaniverma7056, 1 year ago

The sum of ages of two friends is 20 years. Four years ago the product of their ages was 48.show that these statements can not be true.

Answers

Answered by abhi569
3

 \:  \mathbf{Let   \:  \: present \:  \:  ages  \: of  \: friends  \: are  \:  \: x \:  years  \: and \:  \:  ( 20 - x )  \: years, <br /><br />}


 \bold{Four  \:  \: years \:  \:  ago, }  \\  \bold{<br />Age  \:  \: of  \: friends = ( x - 4 ) \:  \:  years \:  and  \:  \: ( 20 - x - 4 ) = ( 16 - x )  \: years, <br /><br /><br />}



Product of their ages = ( x - 4 ) ( 16 - x )

=> 48 = ( x - 4 ) ( 16 - x )

=> 48 = 16x - x² - 64 + 4x

=> x² - 20x + 112 = 0


 \bold{<br />On  \: comparing  \: the  \: given \:  equation \:  with ( ax ^{2}  + bx + c = 0 ),  \:  we  \: get}


a = 1
b = - 20
c = 112



Hence, Discriminant = b² - 4ac

=> ( - 20 )² - 4( 112 × 1 )

=> 400 - 448

=> - 48








 \mathbf{- 48  \: has  \: not  \: any \:  root,  \: Hence \:  this \: cant \:  be  \: used \:  in \:  quadratic \:  equation,  \: due  \: to  \: which \:  the \:  given \:  statement \:  is \:  false} \:
Answered by ItzMahira
7

\purple{\boxed{\huge Answer}}

Given :-

Sum of age of two friends is 20 years.

Let ,

Age of first friend be x

Age of second friend =20-x

Four years ago:-

age of 1st friend = x - 4✔

Age of 2nd friend = (20 - x) - 4 =16 - x✔

Product of the age of two friends = 48 years :-

According to question

=> (x - 4) (16 - x) = 48

=> x (16 - x) - 4 (16 - x) = 48

=> 16x - x² - 64 + 4x = 48

=>- x² + 16x + 4x - 64 - 48= 0

=> - x² +20x - 112 = 0

=> x² - 20x + 112 = 0

Comparing the equation with ax² + bx + c = x² - 20x + 112

Here

a = 1

b = -20

c = 112

Now we will used discriminant formula :-

D = b² - 4ac

=> (-20)² - (4 × 1 × 112)

=> 400 - 448

=> - 48

(D < 0 )i.e D is less than 0 its mean it have no real roots

Hence,

It is not possible to find the present age

Similar questions